Pengaruh Kualitas Pelayanan, Tingkat Pendidikan dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi dengan Sanksi Pajak Sebagai Variabel Moderasi - Abiyyu Al Fadhil Ahmad; Suwandi (PT. Karya Inovatif Nusantara, 2026)
Tax revenue plays an important role in supporting national development, but taxpayer compliance remains a challenge. This study aims to analyze the influence of service quality, education level, and tax socialization on individual taxpayer compliance with tax sanctions as a moderating variable. This research uses a quantitative approach conducted on freelance taxpayers registered at the Primary Tax Office in Gresik. Data were collected through questionnaires and analyzed using multiple regression and moderated regression analysis. The results show that service quality and tax socialization have a positive effect on taxpayer compliance, while education level does not directly affect compliance. Tax sanctions are not able to moderate the relationship between service quality and compliance, but they strengthen the relationship between education level and tax socialization with taxpayer compliance. These findings indicate that improving service quality and strengthening tax socialization supported by consistent tax sanctions can enhance taxpayer compliance. Therefore, tax authorities are recommended to improve service systems and expand tax education programs to increase voluntary compliance.